ANALYSIS OF THE EFFICACY AND EFFECTIVENESS OF SOCIAL EXPENDITURE ON EDUCATION TO ACHIEVE NATIONAL DEVELOPMENT, 2003 -2022 - Quispe Llanos, Renan (2024)
This research explores the dynamics of the education sector in Peru between 2003 and 2022, analyzing trends in government spending, school enrollment, and educational quality. It reveals a steady increase in education spending, although school enrollment varies due to factors such as demographic changes and educational policies. A detailed analysis of the public cost per student at different educational levels shows an increase in investment per student. In addition, key social programs such as PRONAMA, Youth Labor Training, and Beca 18 are examined, highlighting how geographic stratum and income affect participation in these programs. The study concludes by emphasizing the need for more equitable and effective policies to improve the distribution of resources and educational opportunities in the country.